2004
DOI: 10.1002/jpln.200321185
|View full text |Cite
|
Sign up to set email alerts
|

Content and composition of free and occluded particulate organic matter in a differently textured arable Cambisol as revealed by solid‐state 13C NMR spectroscopy

Abstract: Summary ± ZusammenfassungThe composition of functional light soil organic matter pools of arable Cambisols with a gradient in clay content was investigated. Soil texture differences originate from increasing loess admixture to the parent material (coarse-grained tertiary sediments). Using density fractionation in combination with ultrasonic dispersion, two types of particulate organic matter (POM) were obtained: (1) free POM and (2) POM occluded in soil aggregates. Both POM fractions were analyzed by elemental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 41 publications
12
126
3
Order By: Relevance
“…The trend towards increasing degree of transformation from root + litter → fPOM → oPOM → mOM both in C/N ratios and in alkyl-C/O-alkyl-C ratios is consistent with findings from temperate soils (Golchin et al, 1994a,b;Baisden et al, 2002). The results are also in line with systematic differences in composition between fPOM and oPOM reported for soils in climatically different regions (Golchin, 1994a;Kölbl and Kögel-Knabner, 2004). In subtropical soils, Golchin et al (1994b) reported mean alkyl-C/O-alkyl-C ratios of 0.43 (fPOM) and 0.92 (oPOM).…”
Section: Soil Organic Matter Content Composition and Turnover -Genesupporting
confidence: 81%
See 2 more Smart Citations
“…The trend towards increasing degree of transformation from root + litter → fPOM → oPOM → mOM both in C/N ratios and in alkyl-C/O-alkyl-C ratios is consistent with findings from temperate soils (Golchin et al, 1994a,b;Baisden et al, 2002). The results are also in line with systematic differences in composition between fPOM and oPOM reported for soils in climatically different regions (Golchin, 1994a;Kölbl and Kögel-Knabner, 2004). In subtropical soils, Golchin et al (1994b) reported mean alkyl-C/O-alkyl-C ratios of 0.43 (fPOM) and 0.92 (oPOM).…”
Section: Soil Organic Matter Content Composition and Turnover -Genesupporting
confidence: 81%
“…In subtropical soils, Golchin et al (1994b) reported mean alkyl-C/O-alkyl-C ratios of 0.43 (fPOM) and 0.92 (oPOM). Ratios reported for POM in temperate soils indicated POM to be less decomposed and to range from 0.20-0.32 in fPOM, 0.28-0.36 in oPOM (Kölbl and Kögel-Knabner, 2004), 0.37 in mineral associated SOM and 0.44-0.50 in fine earth . In our alpine soils, alkyl-C/O-alkyl-C ratios of the root + litter fraction were similar to those reported previously for agricultural crops including grass-clover roots (Leifeld and Kögel-Knabner, 2005).…”
Section: Soil Organic Matter Content Composition and Turnover -Genementioning
confidence: 94%
See 1 more Smart Citation
“…They confirmed from DRIFT spectroscopy that the oPOM fraction contained more aliphatic compounds than the fPOM fraction. Similar trends were also observed in other studies (Kölbl and Kögel-Knabner 2004;Marín-Spiotta et al 2008;Wagai et al 2008). The higher proportion of aliphatic compounds in the oPOM fraction could have resulted from the selective preservation of recalcitrant aliphatic compounds.…”
Section: Infrared Spectroscopy Of the Density-size Fractionssupporting
confidence: 89%
“…Also the potential for SOC storage by micro-aggregation is signifi cantly aff ected by clay and silt contents (Mayer et al, 2004), turning texture into key factor of C saturation concepts. Results of Kölbl and Kögel-Knabner (2004) showed that even at fi eld scale, the amount of SOC stored as occluded POM may reveal a signifi cant spatial variability, depending on the spatial variation of the clay content. Results of Bornemann et al (2010) confi rmed that the amount of coarse POM in FE can be highly heterogeneous throughout a single agricultural site which was homogeneously managed but also contained variable amounts of RF.…”
mentioning
confidence: 99%